Coriolis flowmeter - Henry, M (United States Patent and Trademark Office, 2016)
A Coriolis flowmeter has a driver that oscillates a conduit, a first sensor configured to generate a first sensor signal indicative of movement of the conduit at a first location, and a second sensor configured to generate a second sensor signal indicative of movement of the conduit at a second location. The first and second locations are arranged so a phase difference between the first and second signals when the conduit is oscillated by the driver is related to a mass flow rate of the fluid through the flowmeter. A digital signal processor includes a plurality of detectors tuned to a set of different frequencies. The detectors are configured to analyze the first sensor signal in parallel and generate an output indicative of how closely an actual frequency of the first sensor signal matches the frequency to which the respective detector is tuned.